Improving 3D-MOHID water model with an upscaling algorithm. (January 2021) - Sobrinho, João; de Pablo, Hilda; Pinto, Lígia; Neves, Ramiro
Abstract: Upscaling methodologies, enforced on nested ocean modelling grids, have become a subject of more intense research due to their benefits in modelling highly dynamic coastal areas. In this paper, an upscaling algorithm is developed for the 3D-MOHID Water model, enabling TwoWay implementations, which considers the nudging of a child domain's velocities, temperature and salinity fields by a parent domain. The algorithm is validated for a schematic case, and then applied to Tagus Region of Freshwater Influence (TagusROFI, Portugal). Results for the schematic case show an improvement of the parent domain while generating minimal mass conservation loss. TagusROFI model domains under TwoWay nesting improved the salinity transition between domain boundaries when reached by the estuarine plume. This new 3D-MOHID Water model feature improves the study of extreme scenarios where OneWay downscaling produces discontinuities on the nested domain's open boundaries, and enables the implementation of higher resolution domains with smaller size grids. Highlights: 3D-MOHID now has an upscaling capability. The algorithm considers nudging of velocity, temperature and salinity fields. Conservation losses computed for a schematic case were negligible. Upscaling improved ocean open boundary transition between grid domains.